Integrating Environmental Education Through Folkloric Practices: A Case Study Of The Greater Adjutant Conservation Movement In India - Dr. Meghna Choudhury; Dr. Umesh Das (Educational Administration: Theory and Practice, 2024)
Traditional practices and customs worldwide, deeply rooted in environmental reverence, form an intrinsic part of folkloric traditions. This paper explores the symbiotic relationship between folklore and environmental education, focusing on the conservation of Greater Adjutant Stork, the world’s second rarest stork species. Endangered and confined to Assam, India, the stork’s conservation journey is led by Dr. Purnima Devi Barman, a wildlife biologist integrating folklore into her efforts. The study examines the role of folklore, encompassing oral literature, material culture, social folk customs, and folk performing arts, in creating awareness and fostering community engagement for nature conservation. Barman’s innovative approach involves the formation of the ‘Hargila Army’, a group of empowered women utilizing traditional weaving skills to weave the stork’s motif on clothes. This not only enhances livelihoods but also spreads conservation messages globally. Folk performances, religious ceremonies, and storytelling are harnessed to change perceptions and integrate the bird into local belief systems. The study delves into the transformative impact of folklore on community attitudes, contributing to increased nests and a thriving population of the once-maligned Greater Adjutant.